Literature on the New Testament in Germany, Holland, and the Scandinavian Countries, 1921–1924 - Windisch, Hans (Harvard theological review, 1926)
A methodological discussion of the value and use of parallels from the history of religion retains its value, especially to-day, when the ‘religionsgeschichtliche Methode’ is rejected even by some scholars of genuine insight. Deissner, a conservative theologian, recognizes in principle the justification of the method, and aims to set the New Testament in its relation to the history of civilization and of religion. He holds the comparison of Christian traditions with kindred non-christian facts to be indispensable, but criticizes the usual method, as employed for instance by Bousset, on the ground that it pays too much attention to the connection of the New Testament with the world of religion outside and too little to the specific nature of Christianity itself. To him, comparison with other religions is a means for determining the connection and contact of the New Testament with the world at large (for example, in the field of language) with the object of showing how incomparable is the New Testament, how underived, real, original — dogmatically speaking, of showing its supernatural character, built up of elements which the conception of a purely immanent cause leaves unexplained. His book is intended to be conciliatory, and formulates in detail various sound principles, such as the distinction between adopting alien religious terminology and filling it with new and distinctive contents. He errs in making the problem too simple and trying to solve it by a dogma. The relations of primitive Christianity to the development of religion in general are too complicated to be covered by the mere distinction between form and contents. It is also a mistake to identify the individual and distinctive with the essential. To the essential elements of primitive Christian tradition belong in fact those which find complete analogy in syncretism and Judaism, and it is dangerous to rest the character of Christianity as revelation on those elements only which a scholar thinks not to be derivative or to have no analogies. Others may think differently, or the missing analogies may be found to-morrow! (See also Bultmann, ThLZ, 1922, no. 10.)